Imposing Connectivity Constraints in Forest Planning Models - Carvajal, Rodolfo; Constantino, Miguel; Goycoolea, Marcos; Vielma, Juan Pablo; Weintraub, Andrés (Operations Research, 2013)
Connectivity requirements are a common component of forest planning models, with important examples arising in wildlife habitat protection. In harvest scheduling models, one way of addressing preservation concerns consists of requiring that large contiguous patches of mature forest are maintained. In the context of nature reserve design, it is common practice to select a connected region of forest, as a reserve, in such a way as to maximize the number of species and habitats protected. Although a number of integer programming formulations have been proposed for these forest planning problems, most are impractical in that they fail to solve reasonably sized scheduling instances. We present a new integer programming methodology and test an implementation of it on five medium-sized forest instances publicly available in the Forest Management Optimization Site repository. Our approach allows us to obtain near-optimal solutions for multiple time-period instances in fewer than four hours.